Mapping of bioclimatic comfort for potential planning using GIS in Aydin - Cetin, Mehmet; Adiguzel, Fatih; Kaya, Omer; Sahap, Ahmet (Springer Science and Business Media LLC, 2016)
People are relaxed (satisfied or well-off) in what is described as comfortable climatic conditions. In such conditions, a person’s energy balance is not disturbed because of stresses from extreme heat or cold. Bioclimatic structure has been well researched and should be a consideration in the planning process for arranging comfortable spaces. It represents the understanding that energy balance is one of the basic elements of a sustainable landscape design. The goals of this study have been to create ideal places for human thermal comfort and to advance objectives focused on the importance of sustainable and ecological landscape planning and design work, along with their accompanying economic benefits. In this study, which focuses on the climate of the Province of Aydin, the most suitable areas for bioclimatic comfort have been identified. The climate values for the Aydin Province have been taken from a total of 22 meteorological stations. Stations at altitudes ranging from 11 to 871 m were used to note the climate changes that occurred. The average temperature, relative humidity, and wind speed from each station, including data collected using Geographic Information System (GIS) software, were transferred. GIS maps were then created from the imported data, and areas of optimal comfort around the city of Aydin were determined. The results show the range that is suitable for a bioclimatic comfort zone in Aydin. The bioclimatic comfort range was determined to be roughly 17 °C for Aydin, and the city of Aydin demonstrated a comfort range between 14 and 19 °C. As a result, the city of Aydin was shown to be a suitable area for bioclimatic comfort.
Keywords: Aydin bioclimatic comfort GIS landscape planning sustainability; 13. Climate action; 11. Sustainability; 15. Life on land; 12. Responsible consumption